2006
DOI: 10.1111/j.1365-2257.2006.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of factor V Leiden and prothrombin G20210A mutations in Chinese patients with deep venous thrombosis and pulmonary embolism

Abstract: Venous thromboembolism (VTE) is a common vascular disease that results in two major clinical manifestations: deep venous thrombosis (DVT) and pulmonary embolism (PE). Several genetic risk factors, especially factor V Leiden and prothrombin G20210A mutations have been reported to be related to VTE in Caucasians, but the relationship remains controversial in other populations. Thus, the objective of the present study was to compare the frequency of the two mutations and also to investigate whether acquired risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
53
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 36 publications
8
53
0
3
Order By: Relevance
“…This implies factor V Leiden and prothrombin G20210A mutations are not genetic risk factors for ONFH in Asians, or at least in the Korean population. Our finding confirms previous reports, demonstrating the absence of these mutations in the Korean and Chinese populations [16,18]. It provides more evidence that the genetic risk profile of ONFH, likewise those of the other hypercoagulable diseases including deep vein thrombosis or pulmonary embolism, may be variable in different ethnic populations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This implies factor V Leiden and prothrombin G20210A mutations are not genetic risk factors for ONFH in Asians, or at least in the Korean population. Our finding confirms previous reports, demonstrating the absence of these mutations in the Korean and Chinese populations [16,18]. It provides more evidence that the genetic risk profile of ONFH, likewise those of the other hypercoagulable diseases including deep vein thrombosis or pulmonary embolism, may be variable in different ethnic populations.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of these genetic variations is associated with a hypercoagulable state, and increases the risk of thromboembolic events. Such phenomena, however, have been observed mainly in Caucasians, and an association between genetic predisposition and thrombotic tendency may differ between ethnic groups [1,13,14,16,20]. Recent studies suggest these genetic predispositions play a role in the risk of ONFH [26,27], but it is unclear whether they apply to non-Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%
“…PRT 20210G>A is the second most common thrombophilic polymorphism in Caucasians, associated with the risk of thrombosis with an estimated population frequency of 2-3% in healthy people and 6.2% in VTE patients [21]. In comparison with previous studies conducted by Mathonnet et al and Jun et al [22,23] had similar results in the frequency of factor V Leiden and Prothrombin gene mutation. Mathonnet et al, Jun et al reported FVL and PRT gene mutations to be totally absent in Moroccan an and Chinese VTE patients [22,23].…”
Section: Discussionsupporting
confidence: 65%
“…This situation necessitates the generation of several appropriate age-dependent reference ranges to interpret laboratory data in pediatric patients and prevent misclassification of children having defects of factors and inhibitors of the coagulation system (7). Since there are differences in the hemostatic system among different racial/ethnic groups (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and also between different analyzer and reagent systems (4), coagulation laboratories should develop age-related reference ranges specific to their own testing systems for the local population (4,7,32). In this study, we analyzed retrospectively the results of preoperative APTT testing in childhood and adult controls undergoing minor elective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…VTE is not as common in Chinese as in Caucasians (15). Genetic risk factors related to VTE in Caucasians such as factor V Leiden and prothrombin G20210A mutations are rare in Asian, especially in Chinese and Japanese (16)(17)(18)(19)(20)(21)(22). The mean plasma concentrations of factors VII, VIII and fibrinogen were lower in Japanese than in Caucasians (23).…”
Section: Introductionmentioning
confidence: 99%